IGCSE physics - Duncan, Tom, 1922-2007; Kennett, Heather (London : John Murray, 2002)
This international edition of GCSE Physics has been designed to provide up-to-date and comprehensive coverage of the core and supplementary topics specified in the IGCSE Physics syllabus. Amendments have been made throughout the text and the illustrations to fulfil these aims. In particular: wave theory is introduced and more details of a range of ultrasonic echo techniques such as medical ultrasound imaging are included factors affecting stopping distance are analyzed in detail and the section of satellites has been expanded volume expansion in solids, liquids and gases are compared and the term thermal capacity is explained the concept of electric fields and emf have been introduced, along with applications of potential divider circuits and the principles of ink-jet printers and magnetic recording have been added sources of background radiation hazards, nuclear stability and radioisotopes and their uses are reviewed investigations which are suitable for conection to a datalogger and computer have been identified throughout the text general advice on practical work is provided along with suggestions for more advanced investigations numerous questions from recent IGCSE examination papers have been included.
Physics and technology; scientific enquiry; light rays; reflection of light; plane mirrors; refraction of light; total internal reflection; lenses; simple optical instruments; additional questions; mechanical waves; electromagnetic radiation; sound waves; musical notes; additional questions; measurements; density; weights and stretching; molecules; additional questions; moments and levers; centres of gravity; adding forces; energy transfer; pressure in liquids; floating and sinking; additional questions; velocity and acceleration; graphs and equations; falling bodies; force and acceleration; momentum; kinetic and potential energy; circular motion; additional questions; thermometers; expansion of solids, liquids and gases; the gas laws; specific heat capacity; latent heat; conduction and convection; radiation; energy sources; additional questions; static electricity; potential difference; resistance; capacitors; electric power; electricity in the home; additional questions; magnetic fields; electromagnets; electric motors; electric meters; generators; transformers; additional questions; electrons; radioactivity; atomic structure; revision questions mathematics for physics; experimental physics; experiments; answers.
Includes index.
1
Keywords: Physics -- Textbooks; Physics -- Examinations -- Study guides; Physics -- Problems, exercises, etc